Manejo da densidade em plantações clonais de Tectona grandis Linn. f. no estado de Mato Grosso - Madi, João Paulo Sardo (2018)
This study aimed to develop a density management diagram for clonal commercial stands of Tectona grandis Linn.f in the State of Mato Grosso. The study was conducted in commercial stands in Midwest of the state of Mato Grosso, Brazil. Data were collected from clonal stands of up to 8 years of rotation, collected in circular sample plots, in a total of 587 plots, varying in area from 359 to 616 m2 . The site yield capacity was obtained through dominant height and the site curves through guide curve method, using the Schumacher model. The DMD related the variables number of plants per hectare (N), quadratic mean diameter (dg), dominant and average codominant height (hd), volume (V) and stand density index (IDP) from Reineke model, with fixed exponent of -1,605. The ideal management stripes were based on the study by Kumar et al. (1995) and Minoche et al. (2017). For representation of dominant height and volume isolines, the system of equations proposed by Dean and Baldwin (1993) was used. Statistics of root mean squared error (RMSE), relative root mean squared error (RMSE (%)) and the squared coefficient of correlation (R2 ) were used to verify the quality of the fitted models. Two scenarios were simulated from DMD. In the first one, the objective was the production of logs of smaller dimensions and shorter rotations. The other scenario was the production of larger logs and longer rotations for sawmill. The Schumacher model for site presented satisfactory statistics, with values of RMSE % near 14% and 83,71% of R2 . The estimation models of quadratic diameter, as well as volume, also presented good statistics, showing RMSE % values of 3,03 and 1,84 and R2 of 99,37% and 99,81%, respectively. In the first scenario only one thinning was necessary to achieve the average quadratic diameter of 25 cm and stand volume of 193,3 m3 /ha. For presenting a longer rotation cycle, two thinnings were necessary in the second scenario, where an average quadratic diameter of 35,7 cm and volume of 186 m3 /ha were achieved. With this case study, it was possible to imply that thinnings are occurring early in the areas studied, demonstrating, therefore, the necessity of revisions in the frequency of thinnings.